PEMBANGUNAN PARIWISATA DI PULAU NAU KABUPATEN WAROPEN PROVINSI PAPUA - ERARI, ABERT NIKOLAS; OGOTAN, MARTHA; RARES, JOYCE JACINTA (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this research is to know Tourism Development In Pilau Nau Waropen Regencyof Papua Province. This research uses quantitative approach method. Tourism Development Can be seenfrom three Indicators about Tourism Development proposed by Djoko Wijono Namely Akstraksi (Promote),Amenitas (Provision of Facilities), and Aksebilitas (infrastructure facilities). The research informants wereHead of Tourism, Head of Object and Attractions, Head of Tourism Destination Management Section,Tourist, totaling 6 people. Data was collected using interview guidelines, while the analytical technique usedwas interactive model analysis from Miles and Hubernan.Based on the result of data analysis, it is concluded that the Tourism Development In Nau Islandis seen from the indicator of Akstraksi (Promosikan), Amenitas (Provision of Facilities) is still not good.Based on the research results can be recommended suggestions: 1. In the development of Nau Islandtourism in Waropen district, local government khsusnya Tourism Department needs to promote tourism bymaking events Waropen cultural festival as a way to attract tourists sympathy towards Waropen island. Inaddition Tourism Department should be intensely promoting through the website for outside tourists to knowthe beauty of tourism island Nau. 2. In order for Nau Island tourism to become a favorite tourist destinationfor both local and foreign tourists, the local government through the Tourism Department should buildhotels and cellular networks, because if seen in the field that the problem of lodging and cellular jeringanis still a major obstacle for tourists.Keywords: Tourism Development.